2020
DOI: 10.1186/s12915-020-00854-9
|View full text |Cite
|
Sign up to set email alerts
|

Independent glial subtypes delay development and extend healthy lifespan upon reduced insulin-PI3K signalling

Abstract: Background The increasing age of global populations highlights the urgent need to understand the biological underpinnings of ageing. To this end, inhibition of the insulin/insulin-like signalling (IIS) pathway can extend healthy lifespan in diverse animal species, but with trade-offs including delayed development. It is possible that distinct cell types underlie effects on development and ageing; cell-type-specific strategies could therefore potentially avoid negative trade-offs when targeting diseases of agei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 65 publications
2
11
0
Order By: Relevance
“…S1 B ). In addition, and consistent with previous studies examining the effects of reduced IIS in glia ( 31 ), we observed no change in fecundity for flies overexpressing FOXO in glia ( SI Appendix , Fig. S1 C ).…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…S1 B ). In addition, and consistent with previous studies examining the effects of reduced IIS in glia ( 31 ), we observed no change in fecundity for flies overexpressing FOXO in glia ( SI Appendix , Fig. S1 C ).…”
Section: Resultssupporting
confidence: 92%
“…Our results also place glial cells alongside the fat body ( 24 ) and some gut cell populations ( 20 ) as Drosophila cell types in which FOXO can mediate similar effects. Our results also complement our recent findings that glia-specific IIS inhibition can extend healthy lifespan in a FOXO-dependent manner ( 31 ). Finally, our results do not exclude the possibility that other TFs downstream of IIS in the nervous system can modulate longevity; indeed, recent studies have shown that knockdown of the ETS family TF Eip74EF in neurons can extend healthy lifespan ( 20 ), and other TFs are likely to play additional roles in nervous system aging.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…However, it remained unclear whether it is mediated by the loss of Irs2 in neurons or astrocytes or both. A recent study used genetic manipulations of the IIS pathway in different glial subtypes in the Drosophila brain and found that reduced insulin/PI3K signaling specifically in astrocyte‐like glia, but not in other glial subtypes, extends lifespan without delaying development and this effect is FoxO3 dependent (Woodling et al, 2020 ). Our result that the subcellular localization of FoxO3 in astrocytes is highly sensitive to insulin/PI3K signaling is in keeping with this idea and supports a conserved astrocytic insulin/PI3K/FoxO3 pathway in metabolism and lifespan regulation.…”
Section: Discussionmentioning
confidence: 99%
“…Key to the regulation of aging and metabolism are the Forkhead box O (FoxO) transcription factors, which act downstream of the insulin/insulin‐like growth factor signaling (IIS) pathway to mediate critical organismal processes, including growth control, reproduction, and lifespan regulation, and cellular responses such as energy utilization, metabolic homeostasis, autophagy, and stress resistance (Barthel et al, 2005 ; Brown & Webb, 2018 ; Gross et al, 2008 ; Martins et al, 2016 ). In both Caenorhabditis elegans and Drosophila melanogaster , reduction of IIS signaling leads to extended lifespan, and this effect requires FoxO/DAF16 and dFOXO, respectively (Friedman & Johnson, 1988 ; Friedman & Johnson, 1988 ; Kenyon et al, 1993 ; Woodling et al, 2020 ). This pathway is well‐conserved as FoxO3, the most prominent FoxO member in the mammalian system, is implicated in lifespan extension in caloric‐restricted mice (Shimokawa et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%